Stihijski (ne)razvoj neurbaniziranega dela mesta na primeru Ljubljane - Smrekar, Aleš (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
Urbanization causes changes within cities and their surrounding areas and deviates from the concepts of sustainable development. The main cause of current condition is the lack of an adequate relation towards the environment.In narrow water-protection zones in the area of Ljubljansko Polje there are areas without any contents, if we donćt take into account water pumping, which enables allotment gardening, uncontrolled taking of water and gravel and waste dumping. The municipality has made first steps towards the rehabilitation of the degraded landscape.
Keywords: mesta; urbanizacija; raba tal; odpadki; ravnanje z odpadki; odlagališča; divja odlagališča; onesnaževanje voda; podtalnica; vodni viri; varstvo okolja; environmental protection; Ljubljana